Peran Komunikasi Organisasi Bagi Pimpinan Menengah di The Highland Park Resort & Hotel Bogor - Nadya Annisa Putri (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research analyzes the role and communication styles of middle managers at The Highland Park Resort & Hotel Bogor in managing organizational communication and employee development. Using a qualitative approach with in-depth interviews, observation, and documentation studies, it was found that managers effectively fulfill roles as a mentors, information controllers, external input seekers, and inter-departmental liaisons, while actively avoiding isolation. Regarding communication styles, they combine a responsive and equal approaches, structured communication, dynamic target achievement, and open to team ideas, and rarely use a controlling or avoiding styles. This dynamic and integrated combination of roles and styles enables managers to build strong relationships, manage team dynamics, and create a productive work environment. These findings affirm the importance of adaptive leadership communication for operational efficiency at The Highland Park Resort & Hotel Bogor.